Peningkatan Efektivitas Pembelajaran Melalui Strategi Pembelajaran - M Muthma'innah; Faisal Amri; Frangky Silitonga (TADRIBUNA, 2024)
Increasing the effectiveness of learning requires paying attention to appropriate learning strategies. This article aims to determine the increase in learning effectiveness through learning strategies. This article is the result of a literature review based on related books and journals. Increasing the effectiveness of learning can be done by choosing the right learning strategy. The selection of learning strategies must pay attention to certain criteria or standards, such as learning objectives, material, student characteristics, educational staff, and time.